Problems associated with controlling the texture of metallic materials - Zaveryukha, Anatoly A. (Materiali in tehnologije, 2004)
In this paper we consider some of the problems associated with the texture control of metallic materials during such processes as recovery, primary, collecting (normal grain growth) and secondary recrystallization. The study focuses on the most extensively studied electrical steels and takes account of well-known and assumed influencing mechanisms involving chemical elements and aluminium nitride particles dissolved in solid solution during the formation of the steel's microstructure and texture. We concluded that the two main, influential mechanisms are as follows: first, inhibiting of the recovery and recrystallization processes; second, the energy changes associated with the grains of different orientation. It is assumed that the energy fields being created by the nitride particles are significant when it comes to slowing down growth and selecting the direction of the grain-boundarymobility. Two hypotheses were advanced relating to the asymmetry of the grain boundaries' properties and the availability of grains with different energies, which make it possible to explain the secondary-recrystallization process.
Keywords: kovinski materiali; nitriranje; rekristalizacija; struktura; tekstura; zrna; nitridi